Arts in Hospitals during COVID-19: Time to Reflect, hosted by CW+ (the charity for Chelsea & Westminster NHS Hospitals Foundation Trust), 22 January 2021, online. (1st December 2021) - Gray, Karen
Review of: Arts in Hospitals during COVID-19: Time to Reflect, hosted by CW+ (the charity for Chelsea & Westminster NHS Hospitals Foundation Trust), 22 January 2021, online